Breast cancers with a BRCA1-like DNA copy number profile recur less often than expected after high-dose alkylating chemotherapy - Schouten, Philip; Marmé, Frederik; Aulmann, Sebastian; Sinn, Peter; Essen, Hendrik F. van; Ylstra, Bauke; Hauptmann, Michael; Schneeweiss, Andreas; Linn, Sabine C. (Clinical cancer research, 2015)
Purpose: Breast cancers in carriers of inactivating mutations of the BRCA1 gene carry a specific DNA copy-number signature (“BRCA1-like”). This signature is shared with cancers that inactivate BRCA1 through other mechanisms. Because BRCA1 is important in repair of DNA double-strand breaks through error-free homologous recombination, patients with a BRCA1-like tumor may benefit from high-dose alkylating (HD) chemotherapy, which induces DNA double-strand breaks. - Experimental Design: We investigated a single institution cohort of high-risk patients that received tandem HD chemotherapy schedule comprising ifosfamide, epirubicin, and carboplatin or conventional chemotherapy. We classified copy-number profiles to be BRCA1-like or non-BRCA1-like and analyzed clinical associations and performed survival analysis with a treatment by biomarker interaction design. - Results: BRCA1-like status associated with high-grade and triple-negative breast cancers. BRCA1-like cases benefitted from the HD compared with a conventional regimen on disease-free survival (DFS): [hazard ratio (HR), 0.05; 95% confidence interval (CI), 0.01-0.38; P = 0.003]; distant DFS (DDFS): (HR, 0.06; 95% CI, 0.01-0.43; P = 0.01); and overall survival (OS; HR, 0.15; 95% CI, 0.03-0.83; P = 0.03) after correction for prognostic factors. No such benefit was observed in the non-BRCA1-like cases on DFS (HR, 0.74; 95% CI, 0.38-1.46; P = 0.39), DDFS (HR, 0.79; 95% CI, 0.41-1.52; P = 0.47), and OS (HR, 0.93; 95% CI, 0.52-1.64; P = 0.79). The P values for interaction were 0.01 (DFS), 0.01 (DDFS), and 0.045 (OS). - Conclusions: BRCA1-like tumors recurred significantly less often after HD than conventional chemotherapy. BRCA1-like copy-number profile classification may be a predictive marker for HD alkylating chemotherapy. Clin Cancer Res; 1-8. ©2014 AACR.
Published online first December 5, 2014
Gesehen am 14.07.2020